Desain LinTar materi Daerahku dan Kekayaan Alamnya meningkatkan Adversity Quotient & Self Management Kelas IV SD Plus Sunan Pandanaran - N., Frika Trisetya; Fatih, Mohamad; Alfi, Cindya (Universitas Nusantara PGRI Kediri, 2024)
The purpose of this study was to determine whether there was an increase in fourth grade students of SD Plus Sunan Pandanaran Blitar district regarding Adversity Quotient and Self Management skills. Research and Development (RnD) was used as the method in this study with waterfall as the model. Questionnaires, interviews and documentation were used to collect research data. Media, Material and Language experts acted as media validity testers. The assessment from the media expert scored 96.1% in the